2014
DOI: 10.4000/com.7140
|View full text |Cite
|
Sign up to set email alerts
|

Histoire d’une innovation agricole récente à l’échelle régionale : quelle différenciation des sorghos repiqués dans le bassin du lac Tchad ?

Abstract: Frontière des hommes, frontière des plantes cultivées : diffusions et recompositions de l'agro-biodiversité

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The three sorghum types are thus not well individualized genetic entities despite their distinct names, morphological differences, and differences in organs of interest for each cultivated type. Similar results were reported by [34] on rainfed and transplanted sorghum in the Lake Chad basin. In addition, some authors have shown that differences within a species can also be due to the influence of the environment [35].…”
Section: Discussionsupporting
confidence: 90%
“…The three sorghum types are thus not well individualized genetic entities despite their distinct names, morphological differences, and differences in organs of interest for each cultivated type. Similar results were reported by [34] on rainfed and transplanted sorghum in the Lake Chad basin. In addition, some authors have shown that differences within a species can also be due to the influence of the environment [35].…”
Section: Discussionsupporting
confidence: 90%